Generation of buffalo embryonic stem cell-like cells from in vitro produced, day 8 hatched and day 9 expanded blastocysts - Kumar, D; Anand, T; Singh, K P; Shah, R A; Singh, M K; Chauhan, M S; Palta, P; Singla, S K; Manik, R S (The Indian Journal of Animal Sciences, 2012)
The present study was taken up to isolate ICM cells from in vitro fertilized blastocysts for generation of BuES cell- like cells. A total of 69 hatched (HBs) and 84 expanded blastocysts (ExBs) were used for the isolation of ICM cells. The total cell number of day 8 HBs (149.3 ± 2.06) was significantly more than that of the day 9 ExBs (123.6 ±1.72). The attachment and primary colony formation rate of HBs was significantly higher over the ExBs, and time required for the attachment of ICMs to the feeder layer and primary colony formation was significantly low in HBs. After continuous sub-passage of primary colony obtained from HBs and ExBs, the cells were grown up to 11 and 6 passages, respectively. BuES cell-like cells appeared healthy, proliferative and exhibited dome shaped morphology, expressed alkaline phosphatase and had a normal karyotype. BuES cell-like cells also expressed OCT-4 and NANOG and differentiated in to neuron like cells in the presence of all-trans retinoic acid. These differentiated cells expressed NF-68 gene. Thus intact method for isolation of ICMs from HBs (day 8) proved to be a superior method for generation of BuES cell-like cells than enzymatic method for ExBs (day 9).